2018
DOI: 10.33546/bnj.389
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Family Support and Relapse in Schizophrenia at the Psychiatric Hospital

Abstract: Background: Schizophrenia is a severe mental illness with the majority of patients’ experiences relapses. Family support is not a new topic, but still considered as an important factor to prevent the relapse. However, little is known about the correlation between family support and relapse in schizophrenia patients in North Sumatra, Indonesia.Objective: This study aims to examine the relationship between family support and relapse in schizophrenia.Methods:  This was a correlational cross sectional study conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…[37][38][39] Family support reduces relapse and improves clinical outcomes. [40] Our instrument may not have captured the specific aspects of social support crucial for treatment adherence. Similarly, stigma was not linked to missed appointments, contradicting previous research on its influence on healthcareseeking behavior among those with mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Family support reduces relapse and improves clinical outcomes. [40] Our instrument may not have captured the specific aspects of social support crucial for treatment adherence. Similarly, stigma was not linked to missed appointments, contradicting previous research on its influence on healthcareseeking behavior among those with mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…Relapse episodes can progressively decrease the patient's ability to function, worsening patient response to medication and clinical prognosis. The occurrence of relapse is reported to be dependent on the family [12], [25], aside from medication adherence and presence of stressors. Our study shows that most patients with schizophrenia who are employed receive high appraisal support from their family as they are trusted to participate in activities outside the home, albeit still under supervision and guidance from the family.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated the relationship between family support and care environment for patients with schizophrenia, including quality of life. Family support has been reported to significantly impact the decrease in symptom recurrence after discharge [10] and decrease in relapse [11], [12]. One study examining family support and quality of life among persons with schizophrenia mentions family support without providing details on the components of support [10].…”
Section: Issn: 2252-8806 mentioning
confidence: 99%
See 1 more Smart Citation
“…Oleh karena itu, keluarga dan anggota masyarakat non-ODS seharusnya bisa menjadi salah satu wahana penyembuhan ODS melalui sikap dan perilaku sosial yang tepat. Beberapa penelitian telah membuktikan bahwa dukungan keluarga yang baik dapat menurunkan angka kekambuhan pada ODS (Latipun, 2016;Simanullang, 2018).…”
Section: Pendahuluanunclassified